2007
DOI: 10.1099/vir.0.82643-0
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of African orthobunyaviruses

Abstract: The genus Orthobunyavirus is composed of segmented, negative-sense RNA viruses that are responsible for mild to severe human diseases. To date, no molecular studies of bunyaviruses in the genus Orthobunyavirus from central Africa have been reported, and their classification relies on serological testing. Four new primer pairs for RT-PCR amplification and sequencing of the complete genomic small (S) RNA segments of 10 orthobunyaviruses isolated from the Central African Republic and pertaining to five different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 12 publications
0
7
1
Order By: Relevance
“…Unlike for BWAV and PGAV, the relative position identified by our analysis for NDV was not consistent with a previous report examining the S segment sequence of NDV (strain ArB16055) [21]. This previous study had suggested a close genetic relationship to Bunyamwera virus, an observation that was apparently at odds with serological evidence assigning NDV to a distinct serogroup [19].…”
Section: Discussioncontrasting
confidence: 96%
See 1 more Smart Citation
“…Unlike for BWAV and PGAV, the relative position identified by our analysis for NDV was not consistent with a previous report examining the S segment sequence of NDV (strain ArB16055) [21]. This previous study had suggested a close genetic relationship to Bunyamwera virus, an observation that was apparently at odds with serological evidence assigning NDV to a distinct serogroup [19].…”
Section: Discussioncontrasting
confidence: 96%
“…Together with repeated isolations from mosquito pools [17], [18], [20] these findings indicate that, as with many of the African orthobunyaviruses, NDV virus might also be much more prevalent than is currently appreciated. Intriguingly, the limited sequencing data previously available for this virus suggests that Nyando virus (strain ArB16055; GenBank Accession AM709781) is closely related to Bunyamwera virus [21], a finding that appears to be at odds with the lack of serological cross-reactivity between these viruses. Indeed Nyando virus is classified into a distinct serogroup (Nyando serogroup), of which it is presently the only member [22].…”
Section: Introductionmentioning
confidence: 98%
“…mosquitoes collected in the Semliki Forest in Uganda [1]. Based on detection of antibodies to BUNV in human sera and isolations of BUNV from patients suffering febrile illness, the virus is widely distributed in several regions of sub-Saharan Africa [2]–[4]. BUNV is maintained in nature by a propagative cycle involving blood-feeding mosquitoes and susceptible vertebrate hosts, probably small rodents [5].…”
Section: Introductionmentioning
confidence: 99%
“…Comprehensive molecular genetic studies have involved viruses in only four serogroups, namely, Bunyamwera, group C, California, and Simbu (5,12,26,27), but recently S-segment nucleotide sequences have been obtained for one or two representatives of the Bakau, Bwamba, Nyando, and Turlock serogroups (20,35). In all cases the S genome segment encodes two proteins, N and, in an overlapping open reading frame (ORF), a small nonstructural protein termed NSs.…”
mentioning
confidence: 99%